The effect of traditional games on children's social attitudes in Physical education learning - Juyinah Juyinah; Dicky Oktora Mudzakir (Universitas Suryakancana, 2022)
The purpose of this study was to determine the effect of traditional games on children's social attitudes in learning physical education. The study used an experimental method, the type of research was one group pretest-posttest design. The sample in this study revealed 20 elementary school age students who were taken randomly in class V MI PUI Sukaperna, Tukdana District, Indramayu Regency. The instrument used in the assessment is a questionnaire that covers the social aspect with 33 items. The type of treatment used is a traditional game using the Direct Instruction learning model. Collecting data using a social attitude questionnaire with the Guttman scale. The results of the research at the time of the initial test were an average of 22.95 and the standard deviation of 6.05 while at the time of the final test the average was 30.60 and the standard deviation was 1.85, this indicates that the influence of traditional games on the children's social attitudes in learning physical education.Keywords: Physical education, Social attitude, Traditional games.